Emotional preparation for the Olympic Games - Botterill, C. (American Swimming Magazine, 1998)
On the question: Is it possible to emotionally prepare for the Olympic Games? Initial answer: It is not easy, and although there are important things an athlete can do, it is probably impossible to totally prepare emotionally for such an experience. Theoretical explanations on emotions and the special situation with the Olympic games and how to deal with it.